Evaluation of the ability of indigenous nematode isolates of Heterorhabditis taysearae and Steinernema kandii to control mango fruit fly Bactrocera dorsalis under laboratory, semi-field and field conditions in Northern Benin. (November 2021) - Godjo, Anique; Chabi, Nadia; Zadji, Lionel; Dossou, Perrin; Batcho, Olive; Baimey, Hugues; Bonou, Wilfried; Sinzogan, Antonio A.C.; Bokonon-Ganta, Aimé; Decraemer, Wilfrida; Willems, Anne; Afouda, Leonard
Abstract: We investigated the use of entomopathogenic nematodes to biologically control Bactrocera dorsalis in mango orchards. One isolate of Steinernema kandii (Thui) and two of Heterorhabditis taysearae (Hessa1 and Korobororou F4) were studied for their invasion time and virulence to third instar larvae of B. dorsalis in laboratory and semi field tests, respectively. In addition, the persistence of the same nematode isolates in soil under field conditions was tested. Results showed that all three nematode isolates could penetrate insect larvae after 2 h of exposure time. Furthermore, under semi field conditions, insect mortality was significantly different among EPN application times. The three nematode isolates were highly pathogenic to B. dorsalis with H. taysearae Hessa1 being the most virulent (70.84% ± 10.46 [SEM] mortality) when EPNs were applied three days before insect introduction in the experimental pots. Moreover, Steinernema kandii persisted in soil up to 32 weeks after nematode application whereas both H. taysearae isolates persisted 30 weeks post application in the mango orchard. In general, four weeks upon nematode application, the density of infective juveniles decreased considerably and remained variable the following sampling dates. Highlights: Entomopathogenic nematodes (EPNs) from Benin were highly pathogenic to B. dorsalis under semi field conditions. Steinernema and Heterorhabditis nematode isolates from Benin could penetrate B. dorsalis insect larvae after 2 h of exposure time. Steinernema kandii and Heterorhabditis taysearae isolates persisted in mango orchards at least 30 weeks post EPN application. Insect mortality was significantly different among EPN application times with H. taysearae Hessa1 being the most virulent when EPNs were applied 3 days before insect introduction in the experimental pots.